Determination of ROC Curve based diagnostic strength of miRNA in ovarian cancer - Rizwana Hussain; Khaliq, Saba (Journal of the Pakistan Medical Association, 2025)
Objective: To examine the diagnostic accuracy of 10 serum-derived micro ribonucleic acids in the early detection of ovarian cancer. Method: The cross-sectional, comparative study was conducted at the Department of Physiology and Cell Biology, University of Health Sciences, Lahore, Pakistan, from February 6, 2018, to August 1, 2021, and comprised women aged 20-70 years diagnosed with ovarian cancer and tentatively planned for surgical procedures. Serum micro ribonucleic acid levels were analysed using quantitative reverse transcription polymerase chain reaction. Data was analysed using SPSS 24, while the micro ribonucleic acid expression profile was analysed using GraphPad Prism. Results: There were 24 women with mean age 44±9.92 years. Cancer antigen 125 had a positive correlation with HSA-miR519d-5p, HSA-miR378-3p, HSA-miR16-5p and HSA-miR21-5p (p<0.05). The diagnostic value of HSA-miR16-5p and HSA-miR21-5p improved from CA125 baseline to CA125 follow-up (6 months after surgery but before chemotherapy), with an area under the curve of 0.56 and 0.82, respectively. The area under the curve for diagnosing cancer stages based on HSA-miR16-5p and HSA-miR21-5p was 0.37 and 0.70, respectively. Conclusion: Cancer-specific micro ribonucleic acids, such as HSA-miR21-5p and HSA-miR16-5p, were found to have diagnostic potential, and could be used in combination with cancer antigen 125 for the screening of ovarian cancer. Key Words: Micro ribonucleic acid, miRNA, Correlation, Expression, Ovarian cancer, CA125.